Social statistics - Blalock, Hubert M. (New York : McGraw-Hill, 1979)
This major reference collection brings together the classic pieces that have framed the often controversial debates of using statistics as a social research method. A strong point of the text is the inclusion of several non-parametric tests in the body of text, so they can be learned at a point suitable type of material being studied with normal assumptions. In summary, the book is a fairly comprehensive textbook to teach students the statistical techniques used in sociology.
Includes bibliographical references and index.
aia 24/07/2017
Loans
Keywords: Statistics; Social Sciences - Statistical method; Social sciences